The war of the worlds - Wells, H. G. (Herbert George), 1866-1946.; Taravella, Daniel (New York : Pocket, 2006)
After Martians land on Earth just outside of London in the late nineteenth century, an Englishman tries to find his wife while the British military and human technology fail in their efforts to stop the Martians, which have begun to kill and feed off of humans.
Includes bibliographical references.
Young Adult
Young Adult
Keywords: Imaginary wars and battles -- Fiction; Life on other planets -- Fiction; Extraterrestrial beings -- Fiction; Imaginary wars and battles -- Fiction; Science fiction; War stories